Outcomes in patients with cardiac amyloidosis and implantable cardioverter-defibrillator. Issue 8 (8th June 2020) - Kim, Eun-Jeong; Holmes, Benjamin B; Huang, Shi; Lugo, Ricardo; Al Aboud, Asad; Goodman, Stacey; Hung, Rebecca R; Slosky, David; Stevenson, William G; Michaud, Gregory F; John, Roy M
Abstract: Aims: Cardiac amyloidosis (CA) is associated with increased mortality due to arrhythmias, heart failure, and electromechanical dissociation. However, the role of an implantable cardioverter-defibrillator (ICD) remains unclear. We conducted case-control study to assess survival in CA patients with and without a primary prevention ICD and compared outcomes to an age, sex, and device implant year-matched non-CA group with primary prevention ICD. Methods and results: There were 91 subjects with CA [mean age= 71.2 ± 10.2, female 22.0%, 49 AL with Mayo Stage 2.9 ± 1.0, 41 transthyretin amyloidosis (ATTR), 1 other] followed by Vanderbilt Amyloidosis centre. Patients with ICD ( n  = 23) were compared with those without ( n  = 68) and a non-amyloid group with ICD ( n  = 46). All subjects with ICD had implantation for primary prevention. Mean left ventricular ejection fraction was 36.2% ± 14.4% in CA with ICD, 41.0% ± 10.6% in CA without ICD, and 33.5% ± 14.4% in non-CA patients. Over 3.5 ± 3.1 years, 6 (26.1%) CA, and 12 (26.1%) non-CA subjects received ICD therapies ( P  = 0.71). Patients with CA had a significantly higher mortality (43.9% vs. 17.4%, P  = 0.002) compared with the non-CA group. Mean time from device implantation to death was 21.8 months in AL and 22.8 months in ATTR patients. There was no significant difference in mortality between CA patients who did and did not receive an ICD (39.0% vs. 46.0%, P  = 0.59). Conclusions: Despite comparable event rates patients with CA had a significantly higher mortality and ICDs were not associated with longer survival. With the emergence of effective therapy for AL amyloidosis, further study of ICD is needed in this group.